Pelaksanaan Eksekusi Benda Bergerak Yang Tidak Dibebani Jaminan Fidusia Di Perkoperasian (Batulis Civil Law Review, 2021)
Guarantee execution is one of the ways when the debtor is negligent in carrying out his obligations which are carried out in accordance with applicable legal procedures. Furthermore, two basic problems are formulated to be studied, namely: 1). How is the execution of movable objects that are not burdened with Fiduciary Guarantees? And 2). What legal efforts can be made by the creditor if the execution of movable objects that are not burdened? this section also describes the purpose and benefits of writing and the originality of research as the work of the real writer. This study uses an empirical juridical approach, data obtained through library research and direct research in the field. Based on the results of the study, it can be concluded that. Judging from the law enforcement theory, the execution of collateral objects with fiduciary guarantees at the Cooperative, namely when the debtor is declared default, the cooperative will seize the object of collateral, takeover or disbursement of collateral objects under the hand, and auction the guarantee object based on the Selling Power. And the creditor's legal efforts according to the theory of legal protection cannot be implemented, namely the cooperative as the creditor will take a non-litigation path such as negotiation and mediation. And if the non-litigation path does not produce results, the cooperative will take a litigation route, namely to file a lawsuit to the court on the basis of a default made by the debtor.
Keywords: Execution; Guarantee; Fiduciary